Lifestyle behaviours associated with 5-year weight gain in a prospective cohort of Australian adults aged 26-36 years at baseline - Kylie J. Smith; Seana L. Gall; Sarah A. McNaughton; Verity J. Cleland; Petr Otahal; Terence Dwyer; Alison J. Venn (BMC, 2017)
Abstract Background Whether not meeting common guidelines for lifestyle behaviours is associated with weight gain is uncertain. This study examined whether 5-year weight gain was predicted by not meeting guidelines for: breakfast consumption (eating between 6 and 9 am), takeaway food consumption (<2 times/week), television viewing (<2 h/day) and daily steps (≥10,000 steps/day). Methods One thousand one hundred and fifty-five Australian participants (43% men, 26-36 years) completed questionnaires and wore a pedometer at baseline (2004-06) and follow-up (2009-11). Weight was measured or self-reported, with a correction factor applied. For each behaviour, participants were classified according to whether they met the guideline: consistently met at baseline and follow-up (reference group); not met at baseline but met at follow-up; met at baseline but not met at follow-up; consistently not met at baseline and follow-up. For each behaviour, weight gain was calculated using linear regression. Weight gain by number of guidelines met was also examined. Results Mean 5-year weight gain was 2.0 kg (SD:6.3). Compared to the reference group, additional weight (mean, 95% CI) was gained among those who did not meet the guideline at follow-up, or consistently did not meet the guideline, for breakfast (1.8 kg, 0.7-2.9; 1.5 kg, 0.1-2.8); takeaway food (2.2 kg, 0.7-3.6; 1.9 kg, 0.7-3.1); watching television (1.9 kg, 0.9-2.9; 1.4 kg, 0.4-2.3); and daily steps (2.6 kg, 1.1-4.04; 1.6 kg, 0.5-2.7). Those who met ≤1 guideline at follow-up gained 3.8 kg (95% CI 2.3-5.3) more than those meeting all guidelines. Conclusion Individuals who adopted healthier behaviours between baseline and follow-up had similar weight gain to those who met the guidelines at both time points. Encouraging young adults to meet these simple guidelines may reduce weight gain.